Geotechnical Behavior Of Shell Footings - Alraziqi, Adel Ahmed (2006)
Shell foundations have been considered as the best shallow foundations for transferring heavy load to weak soils, where a conventional shallow foundation undergoes excessive settlement. Due to its economic competitiveness or advantage in areas having high materialtolabor cost ratio, using shell foundations as an alternative to conventional foundations have gained acceptance or adoption in many countries. As it is not economical to study experimentally the geotechnical behaviour of various types of shell footing with different variables, an attempt was made to propose a 2D nonlinear finite element (FE) model by using a commercially available package to assess the geotechnical behaviour of shell footings. Due to configuration complexity of isolated pyramidal and conical shell footings, 3D nonlinear FE models have been proposed. Fullscale tests on shell footings under vertical load were judiciously planned to validate the proposed FE models for modified triangular strip shell footings. Present study also developed equation to estimate the ultimate bearing capacity of inverted triangular shell footings. 2D and 3D FE finite element (FE) models for different types of shell footings namely flat footings, triangular strip shell footings, inverted triangular strip shell footings, conical shell footing and pyramidal shell footings have been developed. Elastoplastic behaviours of soil and foundation have been modelled by DruckerPrager yield criterion and modified Von Mises Criterion. Comparative study between the proposed FE models and published data has been conducted on different existing types of strip shell footings. An experimental work on field has been conducted to study the real behaviour of the proposed shell footings (inverted triangular strip shell footings, triangular strip shell footing and flat footing) under the effects of load transferred from double story residential house. A theoretical model to predict the ultimate bearing capacity equation of the proposed inverted triangular strip shell footings has been developed using theoretical derivations and rupture surface obtained from the FE results. Based on 2D and 3D results obtained, a modified shell footings (inverted triangular strip shell footings) has been proposed and found to be 15 % higher load carrying capacity compared to triangular shell footings. Results also showed that pyramidal shell footings have higher load carrying capacity by 20 % compared to the conical shell footings. The field test results showed that contact pressure of inverted triangular strip shell footings have better distributions when compared to triangular strip shell footings. The stress caused by inverted shell was 20% less than that obtained for triangular shell. An equation for predicting the ultimate bearing capacity of inverted triangular shell footings has been developed. The obtained results have been found in good agreement between FE simulations and field test results. The results of this study suggest that shell footings should come into wider use in the geotechnical field as a serious alternative to shallow and even deep foundations.